Formaldehyde exposure induces autophagy in testicular tissues of adult male rats. Issue 3 (18th October 2013) - Han, Shui‐Ping; Zhou, Dang‐Xia; Lin, Pu; Qin, Zhen; An, Lu; Zheng, Lie‐Rui; Lei, Li
ABSTRACT Formaldehyde, a ubiquitous environmental pollutant, has long been suspected of causing adverse male reproductive effects. However, the molecular and cellular mechanisms underlying this phenomenon remain elusive. The overall aim of this study is to clarify the role of autophagy in male reproductive injuries induced by formaldehyde exposure, by which we can further understand the molecular mechanism of spermatogenesis and develop new targets for prevention and treatment of male infertility. In this study, electron microscopy, Western blot, and RT‐PCR analysis were used to detect autophagy in testicular tissues. Moreover, testicular weights, histopathology, and morphometry were used to evaluate the reproductive injuries of formaldehyde exposure. We found that formaldehyde exposure‐induced autophagy in testicular tissues was dose dependent. Increasing autophagosomes in spermatogenetic cells was observed by electron microscopy in formaldehyde exposure group. In addition, RT‐PCR and Western blot analysis showed the transcription levels of the LC3‐II, as well as the conversion from LC3‐I to LC3‐II, an indicator of autophagy, significantly increased in testicular tissue of formaldehyde exposure group in a dose dependent manner when compared with those in control group. Furthermore, the alterations of autophage were basically consistent with the changes in testicular weight and morphologic findings. In summary, formaldehyde exposure triggered autophagy, and autophagy may be a scathing factor responsible for male reproductive impairment induced by formaldehyde. © 2013 Wiley Periodicals, Inc. Environ Toxicol 30: 323–331, 2015.